Expression quantitative trait loci (eQTLs) in microRNA genes are enriched for schizophrenia and bipolar disorder association signals. Issue 12 (30th March 2015) - Williamson, V. S.; Mamdani, M.; McMichael, G. O.; Kim, A. H.; Lee, D.; Bacanu, S.; Vladimirov, V. I.
Abstract : Background: Schizophrenia (SZ) and bipolar disorder (BD) have substantial negative impact on the quality of human life. Both, microRNA (miRNA) expression profiling in SZ and BD postmortem brains [and genome-wide association studies (GWAS)] have implicated miRNAs in disease etiology. Here, we aim to determine whether significant GWAS signals observed in the Psychiatric Genetic Consortium (PGC) are enriched for miRNAs. Method: A two-stage approach was used to determine whether association signals from PGC affect miRNAs: (i) statistical assessment of enrichment using a Simes test and sum of squares test (SST) and (ii) biological evidence that quantitative trait loci (eQTL) mapping to known miRNA genes affect their expression in an independent sample of 78 postmortem brains from the Stanley Medical Research Institute. Results: A total of 2567 independent single nucleotide polymorphisms (SNPs) ( R 2 > 0.8) were mapped locally, within 1 Mb, to all known miRNAs (miRBase v. 21). We show robust enrichment for SZ- and BD-related SNPs with miRNAs using Simes (SZ: p ≤ 0.0023, BD: p ≤ 0.038), which remained significant after adjusting for background inflation in SZ (empirical p = 0.018) and approached significance in BD (empirical p = 0.07). At a false discovery rate of 10%, we identified a total of 32 eQTLs to influence miRNA expression; 11 of these overlapped with BD. Conclusions: Our approach of integrating PGC findings with eQTL results can be used to generate specific hypotheses regarding the role of miRNAs in SZ and BD.